PENGARUH BUDAYA ORGANISASI DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN PARUNG PANJANG KABUPATEN BOGOR - Ayu Indah Sari, Putri; Indirasari, Indri (Journal of Research and Publication Innovation, 2024)
This study entitled the effect of organisational culture and communication on employee performance aims to determine the effect of organisational culture and communication on employee performance simultaneously at the Parung Panjang District Office, Bogor Regency. The method used in this research is descriptive method which is associative in nature with a quantitative approach. The population in this study were 50 employees of the Parung Panjang District Office of Bogor Regency with saturated sempel determination obtained 50 respondents. The analysis methods used in this study are validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression test, determination test and significant test (t test and f test). the result of this study is that organisational culture has a significant effect on employee performance with regression Y = 2.959 + 0.8301, the correlation coefficient value is 0.882 where this value can be interpreted that the two variables have a very strong level of relationship. The coefficient of determination is 77.8%. Hypothesis testing obtained t count> t table or (12.978> 1.677). Communication has a significant effect on employee performance with regression Y = 3.062 + 0.886X2, the correlation coefficient value is 0.909 where this value means that the two variables have a very strong relationship level. The coefficient of determination is 82.6%%. Hypothesis testing obtained t count> t table or (15.083> 1.677). Organisational Culture and Communication simultaneously have a significant effect on employee performance with the regression equation Y = 1.955 + 0.341X1 + 0.574X2. The correlation value of 0.925 means that the organisational culture and communication variables have a very strong relationship. The coefficient of determination is 85.5% while the remaining 14.5% is influenced by other factors. Hypothesis testing obtained the value of F count> F table or (138.458> 2.802) thus H0 is rejected and H3 is accepted. This means that there is a simultaneous significant influence between organisational culture and communication on employee performance at the Parung Panjang District Office, Bogor Regency.